Минералогия (Mineralogy) 2019
DOI: 10.35597/2313-545x-2019-5-3-56-69
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy, Geochemistry and Genesis of the Luc Yen Noble Spinel Deposit, Vietnam

Abstract: The paper presents the detailed mineralogical and petrographic study of spinel-bearing marbles at the Luc Yen deposit, North Vietnam. The LA-ICP-MS analysis of 74 spinel grains, combined with mineralogical data, allows us to discriminate them into fve types according to mineral assemblages and trace element geochemistry. Forty seven minerals are identifed as inclusions in spinel grains and 38 minerals are described at Luc Yen deposit for the frst time including leonardsenite, tintisite, manasseite, chalcoalumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Sample VN is the first described example of natural purple spinel in which both Cr 3+ and Co 2+ are the prominent contributors to the coloration and are roughly equally weighted (e.g., similar absorption peak heights above background for each chromophore, resulting in a distinctly purple hue), as opposed to Cr 3+ -(Fe 2+ ,Fe 3+ )-dominant or Fe (Fe 2+ ,Fe 3+ ) alone (e.g., Schmetzer et al, 1989;Malsy and Klemm, 2010). Kuksa et al (2019) presented compositional data and a photograph of a Vietnamese spinel described as "bluish" (within the reference sample known as sample 5), which ap- with minor M Fe 3+ ), which is shown by the greater peak-trough difference in absorption spectrum (figure 10). This is evidently due to the greater visible light absorption by Cr 3+ and particularly Co 2+ per unit of concentration compared to the predominant iron chromophore, Fe 2+ (e.g., ~20× molar absorptiv-Figure 10.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample VN is the first described example of natural purple spinel in which both Cr 3+ and Co 2+ are the prominent contributors to the coloration and are roughly equally weighted (e.g., similar absorption peak heights above background for each chromophore, resulting in a distinctly purple hue), as opposed to Cr 3+ -(Fe 2+ ,Fe 3+ )-dominant or Fe (Fe 2+ ,Fe 3+ ) alone (e.g., Schmetzer et al, 1989;Malsy and Klemm, 2010). Kuksa et al (2019) presented compositional data and a photograph of a Vietnamese spinel described as "bluish" (within the reference sample known as sample 5), which ap- with minor M Fe 3+ ), which is shown by the greater peak-trough difference in absorption spectrum (figure 10). This is evidently due to the greater visible light absorption by Cr 3+ and particularly Co 2+ per unit of concentration compared to the predominant iron chromophore, Fe 2+ (e.g., ~20× molar absorptiv-Figure 10.…”
Section: Discussionmentioning
confidence: 99%
“…One Cr-rich outlier (1111 ppma Cr and 1236 ppma Co; Chauviré et al, 2015) reported from Vietnam is vivid blue in color with no visible reddish or purplish hues, indicating that cobalt has a much higher molar absorptivity than chromium, similar to cobalt's higher molar absorptivity relative to iron (Chauviré et al, 2015). The other outlier, sample 5 of Kuksa et al (2019), has a vivid slightly purplish blue color. Purple spinel sample VN appears to be approximately compositionally intermediate between Cr-dominant pink/red spinels and Co-dominant blue spinels, whereas sample 5 is intermediate between sample VN and Co-dominant blue spinels, as shown in a plot comparing the relative concentrations of Co to Cr, and Co to Fe (figure 12).…”
Section: Chromophore Trace Elements In Spinelsmentioning
confidence: 98%
See 3 more Smart Citations